2019
DOI: 10.33089/jthort.v2i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Study of Weeds as Traditional Medicinal Plants Used by Indigenous People of West Pasaman, Indonesia

Abstract: Ethnobotanical study of weeds as traditional medicinal plants was conducted in West Pasaman,  Indonesia. Weed is a type of wild plant that grows naturally without deliberately planted by humans. Weeds grow around housing residents or farmlands. Their existence is less desirable, but indigenous people in Luhak Nan Tigo, West Pasaman, utilize some types of weeds as traditional medicinal plants. This study was focused on identifying weeds as medicinal plants, disease treated, part of the weeds used, methods of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The data is then compiled into teaching materials which include common names, regional names, scientific names, taxonomy, morphology, content and utilization and then developed into website-based learning media. Daud & Manu, 2021;Demita et al, 2021;Elfrida et al, 2021;Gunarti et al, 2021;Gunawan et al, 2022;Haba et al, 2022;Huda et al, 2022;Jamun et al, 2020;Kissinger et al, 2021;Leksikowati et al, 2020;Maharani et al, 2021;Manurung et al, 2016;Nasution et al, 2021;Ngineikon et al, 2022;Qasrin et al, 2020;Rahmawati & Hidajati, 2017;Ricky et al, 2019;Risnawati & Nurhayatina, 2022;Kemenkes, 2015;Rizki et al, 2019;Rupilu & Watuguly, 2018;Slamet & Andarias, 2018;Sulastri et al, 2021;Suryatinah et al, 2020;Tabeo et al, 2019;Taek et al, 2018;Tima et al, 2020;Wae et al, 2022;Wijana & Rahmawati, 2020;Yansip et Then, instructional analysis is based on the competencies expected in the Kurikulum Merdeka, namely that students are expected to have competencies related to internal factors (identity, ideology, and ideals of Indonesia) and external factors (industrial revolution), namely becoming superior and productive citizens in this Century 21 st . These factors are formulated into six key dimensions, one of which is critical reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…The data is then compiled into teaching materials which include common names, regional names, scientific names, taxonomy, morphology, content and utilization and then developed into website-based learning media. Daud & Manu, 2021;Demita et al, 2021;Elfrida et al, 2021;Gunarti et al, 2021;Gunawan et al, 2022;Haba et al, 2022;Huda et al, 2022;Jamun et al, 2020;Kissinger et al, 2021;Leksikowati et al, 2020;Maharani et al, 2021;Manurung et al, 2016;Nasution et al, 2021;Ngineikon et al, 2022;Qasrin et al, 2020;Rahmawati & Hidajati, 2017;Ricky et al, 2019;Risnawati & Nurhayatina, 2022;Kemenkes, 2015;Rizki et al, 2019;Rupilu & Watuguly, 2018;Slamet & Andarias, 2018;Sulastri et al, 2021;Suryatinah et al, 2020;Tabeo et al, 2019;Taek et al, 2018;Tima et al, 2020;Wae et al, 2022;Wijana & Rahmawati, 2020;Yansip et Then, instructional analysis is based on the competencies expected in the Kurikulum Merdeka, namely that students are expected to have competencies related to internal factors (identity, ideology, and ideals of Indonesia) and external factors (industrial revolution), namely becoming superior and productive citizens in this Century 21 st . These factors are formulated into six key dimensions, one of which is critical reasoning.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a high level of antioxidants is detected in the clove fruit and stem (Al Mashkor 2015). Indigenous people in Luhak Nan Duo also reported the entire plants' consumption, West Pasaman, Sumatra, Indonesia that consumed all parts of the wild grass plant as medicine, such as Oxalis barrelieri, Oxalis corniculata, and Polygala paniculata species as asthma medications (Rizki et al 2019).…”
Section: Growth Form and Partly Used Of Medicinal Plantmentioning
confidence: 99%
“…C. hirta is a shrub and used as a wound healer. Rizki et al [22] reported that this species was one of the traditional medicinal plants by the indigenous people of West Pasaman, Indonesia.…”
Section: Species Richness and Abundance Of Medicinal Plantsmentioning
confidence: 99%